Reinforced pouring type semi-flexible pavement and construction method thereof

By adding modified magnetizable particles and anti-dispersant to the infused semi-flexible pavement, and using neodymium iron boron waste to provide a magnetic field, the magnetic adsorption effect is used to improve the bonding performance between asphalt and cement materials, the problem of easy interface cracks on the semi-flexible pavement is solved and the service life of the road is extended.

CN119711279AActive Publication Date: 2025-03-28TONGJI UNIV

Patent Information

Application Number
CN202510075489.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-28
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

Due to its high stiffness, the filling-type semi-flexible pavement is prone to cracking problems under the influence of driving loads, especially the interface cracks between asphalt and cement materials, which affect the service life of the road and restrict its promotion.

Method used

By adding modified magnetizable particles (Fe3O4) and anti-dispersant to the cement-based grouting material, and adding neodymium iron boron waste to the porous asphalt mixture, the bonding performance between the asphalt and cement material is significantly improved by using the magnetic adsorption effect to reduce the occurrence of interface cracks.

Benefits of technology

It significantly improves the filling rate of grouting materials, enhances the bonding performance of the interface between asphalt and cement materials, effectively reduces the occurrence of interface cracks, and extends the service life of semi-flexible pavements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119711279A_ABST
    Figure CN119711279A_ABST
Patent Text Reader

Abstract

The invention provides a reinforced pouring type semi-flexible pavement and a construction method thereof, modified magnetic particle micron Fe3O4 (at) SiO2 mesoporous microspheres are doped into a cement-based grouting material, an anti-dispersing agent is doped, and the cement-based magnetic grouting material is prepared. Meanwhile, neodymium iron boron waste is doped into the porous asphalt mixture to serve as a magnetic material to provide a magnetic field, and when the cement-based magnetisable grouting material is injected into the porous asphalt mixture, the magnetic grouting liquid can move directionally and be adsorbed at fixed points under the action of the magnetic field by means of the magnetic adsorption effect; the grouting material for the semi-flexible pavement has the advantages that the filling rate of the grouting material is obviously improved, the bonding performance of an asphalt and cement material interface is obviously improved, the generation of interface cracks is effectively reduced, and the service life of the semi-flexible pavement is prolonged. The semi-flexible pavement cement provided by the invention has good compressive strength, breaking strength, tensile strength, bonding strength, fluidity, dry shrinkage rate and the like, and is an ideal base fluid as a cement-based magnetic grouting fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cast-in-place semi-flexible pavement design, and in particular relates to a reinforced cast-in-place semi-flexible pavement and a construction method thereof. Background Art

[0002] Cast-in-place semi-flexible pavement (SFP) material is a composite material with extremely complex composition, structure and interface formed by casting special performance cement-based grouting materials into porous asphalt mixture (PAM). SFP has a high load-bearing capacity and outstanding anti-rutting properties. It has been widely used in heavy-load traffic sections such as road intersections and bus stops as a means of repairing rutting on asphalt pavements. However, in actual engineering applications, semi-flexible pavements are prone to cracking under the action of vehicle loads due to their high stiffness, and the cracking is mostly in the form of interface cracks between asphalt and cement materials, which affects the service life of the road and restricts its large-scale promotion and use. Therefore, how to enhance the interface performance between asphalt and cement materials and reduce interface cracks is an engineering problem that needs to be solved urgently for cast-in-place semi-flexible pavement materials. Summary of the invention

[0003] In view of the deficiencies in the prior art, an object of the present invention is to provide a reinforced cast-in-place semi-flexible pavement and a construction method thereof.

[0004] The present invention intends to learn from the concept of magnetic fluid, add appropriately modified magnetizable particles (Fe3O4) to cement-based grouting materials, and add anti-dispersant to prepare a cement-based magnetic grouting material. At the same time, NdFeB waste is added to the porous asphalt mixture (part of the aggregate is replaced with the same gradation) as a magnetic material to provide a magnetic field. When the cement-based magnetizable grouting material is injected into the porous asphalt mixture, the bonding performance of the interface between the asphalt and cement materials can be significantly improved by means of the magnetic adsorption effect, thereby effectively reducing the generation of interface cracks.

[0005] To achieve the above object, the solution of the present invention is:

[0006] A reinforced grouting type semi-flexible pavement, comprising a magnetizable grouting liquid and a porous asphalt mixture;

[0007] The porous asphalt mixture provides a magnetic field effect. During grouting, the magnetizable grouting liquid moves in a directional manner and is adsorbed at a fixed point under the action of the magnetic field of the porous asphalt mixture. The use of the grouting liquid in the semi-flexible pavement grouting material significantly improves the grouting material filling rate, greatly enhances the asphalt-cement interface performance, reduces the generation of interface cracks, achieves crack-free cast-type semi-flexible pavement materials, and extends the service life of the semi-flexible pavement.

[0008] Wherein, the magnetizable grouting fluid comprises the following components in parts by mass:

[0009] 80-100 parts of Fe3O4@SiO2 mesoporous microspheres, 380-400 parts of cement, 90-100 parts of water, 0.6-2 parts of anti-dispersant;

[0010] The porous asphalt mixture comprises the following components in parts by mass:

[0011] 2-2.50 parts of high viscosity modified asphalt, 55.38-59.35 parts of coarse aggregate, 10.65-14.62 parts of fine aggregate, 23.74-25.44 parts of coarse magnetic aggregate, 4.56-6.26 parts of fine magnetic aggregate, and 2.40-3 parts of filler.

[0012] Furthermore, the total porosity of the porous asphalt mixture is 25%, and the mix design parameters are shown in Table 3.

[0013] Furthermore, the Fe3O4@SiO2 mesoporous microspheres are core-shell structures, the particle size of the mesoporous microspheres is 6-12μm, the core is micron-sized Fe3O4 magnetic particles, the average particle size of the core is 5-10μm; the shell is SiO2, and the average shell thickness is 0.5-1μm.

[0014] Furthermore, Fe3O4@SiO2 mesoporous microspheres use micron-sized Fe3O4 magnetic particles as the core and tetraethoxysilane (TEOS) as the silicon source. The sol-gel method is combined with the template method and the calcination method to coat the mesoporous SiO2 on the surface to synthesize micron-sized Fe3O4@SiO2 mesoporous microspheres with a core-shell structure.

[0015] The specific preparation method is:

[0016] (1) SiO2 shell coating:

[0017] 1) Dispersing the magnetic core: Dispersing micron-sized Fe3O4 particles in ethanol and deionized water, and ultrasonically treating to obtain a uniformly dispersed suspension;

[0018] 2) Introducing silicon source: adding TEOS and 25% molar concentration of ammonia water, stirring and reacting at room temperature;

[0019] 3) Collection and washing: The product was collected by magnetic separation, washed three times with ethanol and deionized water alternately, and dried for later use;

[0020] (2) Formation of mesoporous structure:

[0021] 1) Adding a template: dissolving hexadecyltrimethylammonium bromide or polyethylene oxide as a template in a mixed solution of deionized water and ethanol, adding Fe3O4 particles coated with SiO2, and dispersing by ultrasonication;

[0022] 2) Mesoporous shell formation: TEOS was added dropwise under stirring conditions and the reaction was continued with stirring;

[0023] 3) Cleaning and drying: Collect the samples by magnetic separation and wash them with ethanol and deionized water in sequence;

[0024] (3) Removal of template:

[0025] 1) Place the sample in a ceramic crucible and heat it to 500-600°C at a rate of 5°C / min;

[0026] 2) Maintaining constant temperature for calcination to remove hexadecyltrimethylammonium bromide or polyethylene oxide.

[0027] Furthermore, the cement used is high-performance semi-flexible pavement cement, model is Youlike G30B, the color is black-brown, and it is produced by Zhejiang Weihua New Building Materials Co., Ltd. Its main components are silica fume, water reducer and basalt fine powder.

[0028] Furthermore, the anti-dispersant adopts cement mortar suspension anti-dispersant, which is produced by Guangdong Zhongke Hongtai New Materials Co., Ltd. The anti-dispersant has good anti-dispersibility and fluidity, can reduce the loss of cement, does not bleed water, has controllable setting time, and has anti-seepage of S20 or above, and an anti-corrosion coefficient of not less than 0.85. The anti-dispersant of the present invention functions to disperse the Fe3O4@SiO2 mesoporous microspheres with core-shell structure, so that they are evenly distributed in the grouting liquid and reduce precipitation.

[0029] Furthermore, high-viscosity modified asphalt is prepared by adding high-viscosity modifier to 70# base asphalt, the high-viscosity modifier adopts RST-P type high-viscosity particles produced by Shanghai Pudong Road and Bridge Construction Co., Ltd., and the 70# base asphalt is produced by Sinopec Refining and Sales Co., Ltd.

[0030] Furthermore, the coarse aggregate and the fine aggregate are discontinuously graded, the coarse aggregate is basalt produced by Jiangsu Yabang Mining Co., Ltd., and has a size greater than 2.36 mm, and the fine aggregate is limestone produced by Chibi Yuanda Mining Co., Ltd., and has a size less than 2.36 mm.

[0031] Specifically, compared with continuous grading, discontinuous grading can reduce interference between particles, have fewer isolated voids, larger and more uniform 3D pore structure, larger throat size, better pore connectivity and permeability coefficient, and are more conducive to the penetration of grouting materials in the voids of porous asphalt mixture.

[0032] Furthermore, both the coarse magnetic aggregate and the fine magnetic aggregate are made of NdFeB waste, which is produced by Hengshui Beirui Metal Trading Co., Ltd.

[0033] The present invention uses NdFeB waste as magnetic aggregate to provide magnetic field conditions. The magnetic aggregate has a certain magnetism, and its magnetic force is not enough to allow particles to adsorb and aggregate, but it can adsorb magnetic grouting liquid. The magnetic aggregate is a porous asphalt mixture that is simply and cleverly designed with a magnetic field, the purpose of which is to cooperate with the subsequent magnetic grouting liquid injection. It realizes the utilization of solid waste and reduces material costs, laying a foundation for practical engineering applications.

[0034] Specifically, the grading of magnetic aggregate is consistent with that of aggregate, and NdFeB waste that meets the requirements of coarse aggregate (size greater than 2.36mm) and fine aggregate (size less than 2.36mm) is selected. The mass ratio of magnetic aggregate to aggregate is 3:7, which is equivalent to replacing 30% of the original aggregate. The magnetic aggregate is a porous asphalt mixture with a simple and ingenious magnetic field designed to cooperate with the subsequent magnetic grouting liquid infusion; the adsorption force between the magnetic grouting liquid and the magnetic aggregate optimizes the interface performance, providing a new idea for crack resistance of poured semi-flexible pavement.

[0035] Furthermore, the filler is limestone powder produced by Shanghai Huchang Building Materials Co., Ltd.

[0036] A construction method of the above-mentioned reinforced cast-in-place semi-flexible pavement comprises the following steps:

[0037] Step 1: Prepare high viscosity modified asphalt. The production process is as follows:

[0038] (1) First, the 70# matrix asphalt was heated to liquid at 150°C, and the RST-P high-viscosity particles were preheated at 100°C;

[0039] (2) Secondly, add the specified mass of high-viscosity particles into 70# base asphalt and stir at 180°C and 250 r / min for 30 min to allow the particles to fully swell;

[0040] (3) Then, high-speed shearing was performed at a speed of 4000 r / min for 60 minutes to ensure that the high-viscosity particles were evenly mixed with the 70# matrix asphalt;

[0041] (4) Finally, stir at a speed of 300 r / min for 30 minutes to allow the high-viscosity modified asphalt to fully develop;

[0042] Step 2: Preparation of porous asphalt mixture:

[0043] High-viscosity modified asphalt, coarse aggregate, fine aggregate, coarse magnetic aggregate, fine magnetic aggregate and filler are prepared in the mass ratio of (2-2.50):(55.38-59.35):(10.65-14.62):(23.74-25.44):(4.56-6.26):(2.40-3), and the mixing and transportation process refers to the Technical Specification for Road Pouring Semi-flexible Pavement (T / CECS G:D51-01-2019) to mix the porous asphalt mixture;

[0044] Step 3: Pavement of porous asphalt mixture:

[0045] The main paving process refers to the Technical Specifications for Road Pouring Semi-flexible Pavement (T / CECS G:D51-01-2019);

[0046] (1) Spreading of the mixture: Before paving, use an asphalt spreader to evenly spray the tack coat oil. Use an automatic paver to spread the mixture according to the hot mix and hot paving method. The paving temperature should be 155-165°C. The mixture should be spread evenly without segregation.

[0047] (2) Rolling of the mixture: First, use a 12t double steel wheel roller to vibrate and roll the overlap of the new and old pavement or the junction with the curb for 3 times; then use a 12t steel wheel roller to roll the new pavement excluding the overlap for 5 times using the static pressure method;

[0048] (3) Edge wrapping of the road surface: After the asphalt is paved and compacted, the edge of the road surface is wrapped with polyurethane foam glue and wood strips;

[0049] Step 4: Preparation of Fe3O4@SiO2 mesoporous microspheres:

[0050] The following steps are involved:

[0051] (1) SiO2 shell coating (sol-gel method):

[0052] 1) Dispersing the magnetic core: Dispersing micron-sized Fe3O4 particles in ethanol and deionized water, and ultrasonically treating to obtain a uniformly dispersed suspension;

[0053] 2) Introducing silicon source: adding tetraethoxysilane and 25% molar concentration of ammonia water, stirring and reacting at room temperature;

[0054] 3) Collection and washing: The product was collected by magnetic separation, washed three times with ethanol and deionized water alternately, and dried for later use;

[0055] (2) Formation of mesoporous structure (template method):

[0056] 1) Adding a template: dissolving hexadecyltrimethylammonium bromide or polyethylene oxide as a template in a mixed solution of deionized water and ethanol, adding Fe3O4 particles coated with SiO2, and dispersing by ultrasonication;

[0057] 2) Formation of mesoporous shell: under stirring conditions, tetraethoxysilane is added dropwise and the reaction is continued by stirring;

[0058] 3) Cleaning and drying: Collect the samples by magnetic separation and wash them with ethanol and deionized water in sequence;

[0059] (3) Removal of template (calcination method):

[0060] 1) Place the sample in a ceramic crucible and heat it to 500-600°C at a rate of 5°C / min;

[0061] 2) maintaining a constant temperature for calcination to remove hexadecyltrimethylammonium bromide or polyethylene oxide;

[0062] Step 5: Prepare magnetizable grouting liquid:

[0063] Fe3O4@SiO2 mesoporous microspheres, cement, water and anti-dispersant are added into the mixing tank of the vehicle-mounted mixing and pouring machine in a mass ratio of (80-100):(380-400):(90-100):(0.6-2) for preparation. The preparation process is as follows:

[0064] (1) First add cement, then add Fe3O4@SiO2 mesoporous microspheres, mix the two evenly, and stir for 60 seconds;

[0065] (2) Add water, stir evenly, and stir for 30 seconds;

[0066] (3) Add anti-dispersant, stir evenly, and stir for 30 seconds;

[0067] Step 6: Grouting: When it is confirmed that the laid porous asphalt mixture has cooled to below 50°C, a cement-based magnetizable grouting liquid is poured through a vehicle-mounted mixing and pouring machine (produced by Zhejiang Weihua New Building Materials Co., Ltd.). Under the action of the magnetic field of the porous asphalt mixture, the grouting liquid moves in a directional manner and is adsorbed at a fixed point in the pores. The grouting material has a high filling rate, which enhances the asphalt-cement interface performance, avoids the generation of interface cracks, and prolongs the service life of the semi-flexible pavement.

[0068] Step 7: Scraping: Scraping should be carried out within 5-10 minutes after pouring when no more bubbles come out of the pores of the asphalt mixture. The scraping must be done before the mortar surface crusts. Use a rubber scraper to scrape off excess mortar on the surface to expose the aggregate of the asphalt mixture. In addition, the scraping must be done in the same direction to avoid scratches. At this point, the construction is completed.

[0069] Due to the adoption of the above scheme, the beneficial effects of the present invention are:

[0070] First, the present invention adds modified magnetic particles (Fe3O4) - micron Fe3O4@SiO2 mesoporous microspheres to cement-based grouting materials, and adds anti-dispersants to prepare a cement-based magnetic grouting material. At the same time, NdFeB waste (part of the aggregate is replaced with the same gradation) is added to the porous asphalt mixture as a magnetic material to provide a magnetic field. When the cement-based magnetizable grouting material is injected into the porous asphalt mixture, the magnetic grouting liquid can be directed and adsorbed at a fixed point under the action of the magnetic field by means of the magnetic adsorption effect. The use of semi-flexible pavement grouting materials significantly improves the grouting material filling rate (close to 100%), significantly improves the bonding performance of the interface between asphalt and cement materials, effectively reduces the generation of interface cracks, and extends the service life of the semi-flexible pavement.

[0071] Second, the Fe3O4@SiO2 mesoporous microspheres of the present invention have many advantages such as large specific surface area, uniform size, large pore volume, strong adsorption capacity, protection of the inner core, excellent magnetic properties, and dispersibility, which improve the "carrying and transmission" ability and corrosion resistance of ordinary micron Fe3O4 particles, thereby reducing the segregation of magnetic grouting fluid; the SiO2 coated on the surface can prevent the Fe3O4 particles from contacting with water and air, improve the corrosion resistance, and thus enhance its durability; it solves the segregation and corrosion problems of existing cement-based magnetic grouting fluid (based on ordinary Fe3O4 particles), and further promotes the application of cement-based magnetic grouting fluid in practical engineering.

[0072] Third, the high-performance semi-flexible pavement cement of the present invention has extremely good compressive strength, flexural strength, tensile strength, bonding strength, fluidity, shrinkage rate, etc., and each index exceeds the specification requirements. It is an ideal base liquid for cement-based magnetic grouting fluid, and its performance is significantly better than the ordinary silicate cement of the existing cement-based magnetic grouting fluid.

[0073] Fourthly, the present invention uses NdFeB waste as magnetic aggregate to provide magnetic field conditions, thus realizing solid waste utilization, reducing material costs, and laying a foundation for practical engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 It is a schematic diagram of the composition structure of micron Fe3O4@SiO2 mesoporous microspheres in Example 1 of the present invention.

[0075] Figure 2 It is a schematic diagram of the enhanced cast-in-place semi-flexible pavement structure of Example 1 of the present invention. DETAILED DESCRIPTION

[0076] The invention provides a construction method for a reinforced cast-in-place semi-flexible pavement.

[0077] The present invention is further described below in conjunction with specific examples. This example is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following examples.

[0078] Embodiment 1 (optimum embodiment):

[0079] The construction method of the perfused semi-flexible pavement based on the magnetic grouting fluid of this embodiment comprises the following steps:

[0080] Step 1: Prepare high viscosity modified asphalt. The production process is as follows:

[0081] (1) First, the 70# matrix asphalt was heated to liquid at 150°C, and the RST-P high-viscosity particles were preheated at 100°C;

[0082] (2) Secondly, add the specified mass of high-viscosity particles into 70# base asphalt and stir at 180°C and 250 r / min for 30 min to allow the particles to fully swell;

[0083] (3) Then, high-speed shearing was performed at a speed of 4000 r / min for 60 minutes to ensure that the high-viscosity particles were evenly mixed with the 70# matrix asphalt;

[0084] (4) Finally, the mixture was stirred at a speed of 300 r / min for 30 minutes to allow the high-viscosity modified asphalt to fully develop. The detailed parameters of the high-viscosity modified asphalt are shown in Table 4.

[0085] Step 2: Preparation of porous asphalt mixture:

[0086] High-viscosity modified asphalt, basalt (coarse aggregate), limestone (fine aggregate), NdFeB waste (coarse magnetic aggregate), NdFeB waste (fine magnetic aggregate), and limestone powder (filler) are prepared in a mass ratio of 2.50:59.35:14.62:25.44:6.26:3 (see Table 3). The mixing and transportation process refers to the Technical Specifications for Road Cast-in-Pour Semi-Flexible Pavement (T / CECS G:D51-01-2019) to mix porous asphalt mixture.

[0087] Step 3: Pave porous asphalt mixture. The main paving process refers to the "Technical Specifications for Road Pouring Semi-flexible Pavement" (T / CECS G:D51-01-2019).

[0088] (1) Spreading of the mixture: Before paving, use an asphalt spreader to evenly spray the tack coat oil. Use an automatic paver to spread the mixture according to the hot mix and hot paving method. The paving temperature should be 165°C. The mixture should be spread evenly without segregation.

[0089] (2) Rolling of the mixture: First, use a 12t double steel wheel roller to vibrate and roll the overlap of the new and old pavement (or the junction with the curb) for 3 times; then use a 12t steel wheel roller to statically roll the new pavement except the overlap for 5 times.

[0090] (3) Pavement edge wrapping: After the asphalt is paved and compacted, polyurethane foam glue and wooden strips are used to wrap the pavement edge.

[0091] Step 4: Preparation of Fe3O4@SiO2 mesoporous microspheres:

[0092] The process includes the following steps (taking the modification of 2g micron Fe3O4 particles as an example):

[0093] (1) SiO2 shell coating (sol-gel method)

[0094] 1) Dispersing magnetic cores: 2 g of micronized Fe3O4 particles (average particle size of 5-10 μm) were dispersed in 50 mL of ethanol and 5 mL of deionized water and ultrasonicated for 30 min to obtain a uniformly dispersed suspension;

[0095] 2) Introducing silicon source: adding 1 mL of TEOS and 0.5 mL of ammonia water (25%), stirring and reacting at room temperature for 12 hours;

[0096] 3) Collection and washing: The product was collected by magnetic separation, washed three times with ethanol and deionized water alternately, and dried for later use.

[0097] (2) Formation of mesoporous structure (template method)

[0098] 1) Adding template: Dissolve 0.5 g of CTAB (or P123) as template in a mixed solution of 50 mL of deionized water and ethanol. Add Fe3O4 particles coated with SiO2 (average thickness of 0.5-1 μm) and disperse by ultrasonic for 30 minutes.

[0099] 2) Mesoporous shell formation: 1 mL of TEOS was added dropwise under stirring, and the stirring reaction was continued for 24 hours.

[0100] 3) Cleaning and drying: Collect the samples by magnetic separation and wash them with ethanol and deionized water in sequence.

[0101] (3) Removal of template (calcination method)

[0102] 1) Place the sample in a ceramic crucible and heat it to 600°C (heating rate 5°C / min);

[0103] 2) Maintain constant temperature calcination for 6 hours to remove CTAB or P123.

[0104] like Figure 1 As shown in the figure, the core of Fe3O4@SiO2 mesoporous microspheres (particle size 6-12μm) is micron-sized Fe3O4 magnetic particles, which provide magnetic drive performance; the shell is SiO2, which protects Fe3O4, and the mesopores in Fe3O4@SiO2 mesoporous microspheres carry and transmit the base liquid. Therefore, nano-Fe3O4@SiO2 mesoporous microspheres are prepared by modifying nano-Fe3O4 particles. Due to their unique core-shell structure and mesoporous characteristics, they are mainly used in biomedicine, catalysis, environmental governance and other technical fields.

[0105] Step 5: Prepare magnetic grouting liquid:

[0106] Fe3O4@SiO2 mesoporous microspheres, high-performance semi-flexible pavement cement, water, and cement mortar suspension anti-dispersant are added into the mixing tank of the vehicle-mounted mixing and pouring machine at a mass ratio of 100:400:100:2 for preparation. The preparation process is as follows (the stirring time is based on the preparation of 602g magnetic grouting liquid, and the actual amount of slurry required for the project is determined):

[0107] (1) First add cement, then add Fe3O4@SiO2 mesoporous microspheres, mix the two evenly, and stir for 60 seconds;

[0108] (2) Add water, stir evenly, and stir for 30 seconds;

[0109] (3) Add anti-dispersant and stir evenly for 30 seconds.

[0110] Step 6: Magnetic grouting: When the porous asphalt mixture is confirmed to be cooled to below 50°C, cement-based magnetic grouting is poured through a vehicle-mounted mixing and pouring machine. Under the action of the magnetic field of the magnetic aggregate added to the porous asphalt mixture, the magnetic grouting moves in a directional manner and adsorbs at a fixed point in the pores, significantly improving the grouting material filling rate, greatly enhancing the asphalt-cement interface performance, reducing the generation of interface cracks, and extending the service life of the semi-flexible pavement.

[0111] Step 7: Scraping: Scraping should be done within 10 minutes after pouring when no more bubbles come out of the pores of the asphalt mixture. Scraping must be done before the mortar surface forms a crust. Use a rubber scraper (not a sponge scraper) to scrape off the excess mortar on the surface to expose the aggregate of the asphalt mixture. In addition, the scraping must be done in the same direction (back and forth) to avoid scratches. At this point, the construction is completed.

[0112] Compared with the prior art, the magnetic particles of the cement-based magnetizable grouting material used are ordinary Fe3O4 particles, and the cement is ordinary Portland cement, whose compressive strength, flexural strength, fluidity and shrinkage rate are all worse than those of the high-performance semi-flexible pavement cement of this embodiment (see Table 2).

[0113] Among them, the cement used is high-performance semi-flexible pavement cement, model is Youlike G30B, the color is black-brown, and it is produced by Zhejiang Weihua New Building Materials Co., Ltd.

[0114] The anti-dispersant adopts cement mortar suspended anti-dispersant, which is produced by Guangdong Zhongke Hongtai New Materials Co., Ltd.

[0115] The high viscosity modifier uses RST-P high viscosity particles produced by Shanghai Pudong Road and Bridge Construction Co., Ltd., and the 70# base asphalt is produced by Sinopec Refining and Sales Co., Ltd.

[0116] The coarse aggregate and fine aggregate are discontinuously graded. The coarse aggregate is basalt produced by Jiangsu Yabang Mining Co., Ltd., with a size greater than 2.36 mm, and the fine aggregate is limestone produced by Chibi Yuanda Mining Co., Ltd., with a size less than 2.36 mm. The detailed basic performance indicators of coarse aggregate and fine aggregate are shown in Table 1.

[0117] Both coarse magnetic aggregate and fine magnetic aggregate are made of NdFeB waste and are produced by Hengshui Beirui Metal Trading Co., Ltd.

[0118] The filler is limestone powder, produced by Shanghai Huchang Building Materials Co., Ltd. The detailed basic performance indicators are shown in Table 5

[0119] like Figure 2 As shown, in the cast-in-place semi-flexible pavement of this embodiment, from a microscopic level, NdFeB waste is added to the porous asphalt mixture as a magnetic material to provide a magnetic field. When the micronized Fe3O4@SiO2 mesoporous microspheres in the cement-based magnetic grouting material are injected into the porous asphalt mixture, the magnetic grouting material can move in a directional manner and be adsorbed at a fixed point under the action of the magnetic field by means of the magnetic adsorption effect, which significantly improves the bonding performance of the interface between asphalt and cement materials, improves the filling rate of the grouting material, effectively reduces the generation of interface cracks, and extends the service life of the semi-flexible pavement.

[0120] Embodiment 2:

[0121] The construction method of the cast-in-place semi-flexible pavement of this embodiment comprises the following steps:

[0122] Step 1: Prepare high viscosity modified asphalt. The production process is as follows:

[0123] (1) First, the 70# matrix asphalt was heated to liquid at 150°C, and the RST-P high-viscosity particles were preheated at 100°C;

[0124] (2) Secondly, add the specified mass of high-viscosity particles into 70# base asphalt and stir at 180°C and 250 r / min for 30 min to allow the particles to fully swell;

[0125] (3) Then, high-speed shearing was performed at a speed of 4000 r / min for 60 minutes to ensure that the high-viscosity particles were evenly mixed with the 70# matrix asphalt;

[0126] (4) Finally, stir at a speed of 300 r / min for 30 minutes to allow the high-viscosity modified asphalt to fully develop.

[0127] Step 2: Preparation of porous asphalt mixture:

[0128] High-viscosity modified asphalt, basalt (coarse aggregate), limestone (fine aggregate), NdFeB waste (coarse magnetic aggregate), NdFeB waste (fine magnetic aggregate), and limestone powder (filler) are prepared in a mass ratio of 2:55.38:10.65:23.74:4.56:2.40 (see Table 3). The mixing and transportation process refers to the Technical Specifications for Road Cast-in-Pour Semi-Flexible Pavement (T / CECS G:D51-01-2019) to mix porous asphalt mixture.

[0129] Step 3: Pave porous asphalt mixture. The main paving process refers to the "Technical Specifications for Road Pouring Semi-flexible Pavement" (T / CECS G:D51-01-2019).

[0130] (1) Spreading of the mixture: Before paving, use an asphalt spreader to evenly spray the tack coat oil. Use an automatic paver to spread the mixture according to the hot mix and hot paving method. The paving temperature should be 155°C. The mixture should be spread evenly without segregation.

[0131] (2) Rolling of the mixture: First, use a 12t double steel wheel roller to vibrate and roll the overlap of the new and old pavement (or the junction with the curb) for 3 times; then use a 12t steel wheel roller to statically roll the new pavement except the overlap for 5 times.

[0132] (3) Pavement edge wrapping: After the asphalt is paved and compacted, polyurethane foam glue and wooden strips are used to wrap the pavement edge.

[0133] Step 4: Preparation of Fe3O4@SiO2 mesoporous microspheres:

[0134] The process includes the following steps (taking the modification of 2g micron Fe3O4 particles as an example):

[0135] (1) SiO2 shell coating (sol-gel method)

[0136] 1) Dispersing magnetic cores: 2 g of micronized Fe3O4 particles (average particle size of 5-10 μm) were dispersed in 50 mL of ethanol and 5 mL of deionized water and ultrasonicated for 30 min to obtain a uniformly dispersed suspension;

[0137] 2) Introducing silicon source: adding 1 mL of TEOS and 0.5 mL of ammonia water (25%), stirring and reacting at room temperature for 12 hours;

[0138] 3) Collection and washing: The product was collected by magnetic separation, washed three times with ethanol and deionized water alternately, and dried for later use.

[0139] (2) Formation of mesoporous structure (template method)

[0140] 1) Adding template: Dissolve 0.5 g of CTAB (or P123) as template in a mixed solution of 50 mL of deionized water and ethanol. Add Fe3O4 particles coated with SiO2 (average thickness of 0.5-1 μm) and disperse by ultrasonic for 30 minutes.

[0141] 2) Mesoporous shell formation: 1 mL of TEOS was added dropwise under stirring, and the stirring reaction was continued for 24 hours.

[0142] 3) Cleaning and drying: Collect the samples by magnetic separation and wash them with ethanol and deionized water in sequence.

[0143] (3) Removal of template (calcination method)

[0144] 1) Place the sample in a ceramic crucible and heat it to 500°C (heating rate 5°C / min);

[0145] 2) Maintain constant temperature calcination for 6 hours to remove CTAB or P123.

[0146] Step 5: Prepare magnetic grouting liquid:

[0147] Fe3O4@SiO2 mesoporous microspheres (particle size of 6-12μm), high-performance semi-flexible pavement cement, water, and cement mortar suspension anti-dispersant are added into the mixing tank of the vehicle-mounted mixing and pouring machine at a mass ratio of 80:380:90:0.6 for preparation. The preparation process is as follows (the stirring time is based on the preparation of 602g magnetic grouting liquid, and the actual amount of slurry required for the project is determined):

[0148] (1) First add cement, then add Fe3O4@SiO2 mesoporous microspheres, mix the two evenly, and stir for 60 seconds;

[0149] (2) Add water, stir evenly, and stir for 30 seconds;

[0150] (3) Add anti-dispersant and stir evenly for 30 seconds.

[0151] Step 6: Magnetic grouting: When the porous asphalt mixture is confirmed to be cooled to below 50°C, cement-based magnetic grouting is poured through a vehicle-mounted mixing and pouring machine. Under the action of the magnetic field of the magnetic aggregate added to the porous asphalt mixture, the magnetic grouting moves in a directional manner and adsorbs at a fixed point in the pores, significantly improving the grouting material filling rate, greatly enhancing the asphalt-cement interface performance, reducing the generation of interface cracks, and extending the service life of the semi-flexible pavement.

[0152] Step 7: Scraping. Scraping should be done within 5 minutes after pouring when no more bubbles come out of the pores of the asphalt mixture. Scraping must be done before the mortar surface forms a crust. Use a rubber scraper (not a sponge scraper) to scrape off the excess mortar on the surface to expose the aggregate of the asphalt mixture. In addition, the scraping must be done in the same direction (back and forth) to avoid scratches. At this point, the construction is completed.

[0153] Table 1 Basic performance indicators of aggregate

[0154]

[0155]

[0156] Table 2 Comparison of performance parameters of ordinary Portland cement (42.5R) and high-performance semi-flexible pavement cement

[0157]

[0158] Table 3 Porous asphalt mixture mix design

[0159]

[0160] Table 4 Basic performance indicators of high viscosity modified asphalt

[0161]

[0162] Table 5 Basic performance indicators of mineral powder

[0163]

[0164] The above description of the embodiments is to facilitate the understanding and use of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments. Improvements and modifications made by those skilled in the art based on the principles of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A reinforced perfusion type semi-flexible pavement, characterized in that: It includes a magnetizable grout and a porous asphalt mixture; The porous asphalt mixture provides a magnetic field effect. During grouting, the magnetizable grouting liquid moves in a directional manner and is adsorbed at a fixed point under the magnetic field of the porous asphalt mixture, thereby achieving a crack-free grouting semi-flexible pavement material. Wherein, the magnetizable grouting fluid comprises the following components in parts by mass: 80-100 parts of Fe3O4@SiO2 mesoporous microspheres, 380-400 parts of cement, 90-100 parts of water, 0.6-2 parts of anti-dispersant; The porous asphalt mixture comprises the following components in parts by mass: 2-2.50 parts of high viscosity modified asphalt, 55.38-59.35 parts of coarse aggregate, 10.65-14.62 parts of fine aggregate, 23.74-25.44 parts of coarse magnetic aggregate, 4.56-6.26 parts of fine magnetic aggregate, and 2.40-3 parts of filler.

2. The reinforced perfusion type semi-flexible pavement according to claim 1, characterized in that: The Fe3O4@SiO2 mesoporous microspheres are of core-shell structure, and the particle size of the mesoporous microspheres is 6-12 μm; the core is micron-sized Fe3O4 magnetic particles, and the average particle size of the core is 5-10 μm; the shell is SiO2, and the average shell thickness is 0.5-1 μm.

3. The reinforced perfusion type semi-flexible pavement according to claim 1, characterized in that: The preparation method of the Fe3O4@SiO2 mesoporous microspheres is: (1) SiO2 shell coating: 1) Dispersing the magnetic core: Dispersing micron-sized Fe3O4 particles in ethanol and deionized water, and ultrasonically treating to obtain a uniformly dispersed suspension; 2) Introducing silicon source: adding tetraethoxysilane and ammonia water, stirring and reacting at room temperature; 3) Collection and washing: The product was collected by magnetic separation, washed three times with ethanol and deionized water alternately, and dried for later use; (2) Formation of mesoporous structure: 1) Adding a template: dissolving hexadecyltrimethylammonium bromide or polyethylene oxide as a template in a mixed solution of deionized water and ethanol, adding Fe3O4 particles coated with SiO2, and dispersing by ultrasonication; 2) Formation of mesoporous shell: under stirring conditions, tetraethoxysilane is added dropwise and the reaction is continued by stirring; 3) Cleaning and drying: Collect the samples by magnetic separation and wash them with ethanol and deionized water in sequence; (3) Removal of template: 1) Place the sample in a ceramic crucible and program the temperature; 2) Maintaining constant temperature for calcination to remove hexadecyltrimethylammonium bromide or polyethylene oxide.

4. The reinforced perfusion type semi-flexible pavement according to claim 1, characterized in that: The cement used is high-performance semi-flexible pavement cement, model is Ulico G30B, color is black-brown, and is produced by Zhejiang Weihua New Building Materials Co., Ltd.

5. The reinforced perfusion type semi-flexible pavement according to claim 1, characterized in that: The anti-dispersant is a cement mortar suspension anti-dispersant produced by Guangdong Zhongke Hongtai New Materials Co., Ltd.

6. The reinforced cast-in-place semi-flexible pavement according to claim 1, characterized in that: The high-viscosity modified asphalt is prepared by adding a high-viscosity modifier to 70# base asphalt, the high-viscosity modifier adopts RST-P type high-viscosity particles produced by Shanghai Pudong Road and Bridge Construction Co., Ltd., and the 70# base asphalt is produced by Sinopec Refining and Sales Co., Ltd.

7. The reinforced cast-in-place semi-flexible pavement according to claim 1, characterized in that: The coarse aggregate and fine aggregate are discontinuously graded. The coarse aggregate is basalt produced by Jiangsu Yabang Mining Co., Ltd., with a size greater than 2.36 mm. The fine aggregate is limestone produced by Chibi Yuanda Mining Co., Ltd., with a size less than 2.36 mm.

8. The reinforced cast-in-place semi-flexible pavement according to claim 1, characterized in that: The coarse magnetic aggregate and the fine magnetic aggregate are both made of NdFeB waste and are produced by Hengshui Beirui Metal Trading Co., Ltd.

9. The reinforced cast-in-place semi-flexible pavement according to claim 1, characterized in that: The filler is limestone powder produced by Shanghai Huchang Building Materials Co., Ltd.

10. A construction method of a reinforced cast-in-place semi-flexible pavement as claimed in any one of claims 1 to 9, characterized in that: It includes the following steps: Step 1: Prepare high viscosity modified asphalt. The production process is as follows: (1) First, the base asphalt is heated to a liquid state, and the RST-P type high viscosity particles are preheated; (2) Secondly, add the high-viscosity particles into the matrix asphalt and stir to allow the particles to fully swell; (3) Then shear to ensure that the high-viscosity particles are evenly mixed with the matrix asphalt; (4) Final stirring to allow the high-viscosity modified asphalt to fully develop; Step 2: Preparation of porous asphalt mixture: High-viscosity modified asphalt, coarse aggregate, fine aggregate, coarse magnetic aggregate, fine magnetic aggregate and filler are prepared in the mass ratio of (2-2.50):(55.38-59.35):(10.65-14.62):(23.74-25.44):(4.56-6.26):(2.40-3). The mixing and transportation process refers to the Technical Specifications for Road Pouring Semi-flexible Pavement to mix porous asphalt mixture; Step 3: Pavement of porous asphalt mixture: The main paving technology refers to the "Technical Specifications for Road Pouring Semi-flexible Pavement"; (1) Spreading of the mixture: Before paving, use an asphalt spreader to evenly spray tack coat oil, and use an automatic paver to spread the mixture according to the hot mix and hot paving method. The mixture should be spread evenly without segregation; (2) Rolling of the mixture: First, use a double steel wheel roller to vibrate and roll the joints of the new and old pavement or the junction with the curbstone; then use a steel wheel roller to roll the new pavement except the joints using the static pressure method; (3) Edge wrapping of the road surface: After the asphalt is paved and compacted, the edge of the road surface is wrapped with polyurethane foam glue and wood strips; Step 4: Preparation of Fe3O4@SiO2 mesoporous microspheres: The following steps are involved: (1) SiO2 shell coating: 1) Dispersing the magnetic core: Dispersing micron-sized Fe3O4 particles in ethanol and deionized water, and ultrasonically treating to obtain a uniformly dispersed suspension; 2) Introducing silicon source: adding tetraethoxysilane and ammonia water, stirring and reacting at room temperature; 3) Collection and washing: The product was collected by magnetic separation, washed three times with ethanol and deionized water alternately, and dried for later use; (2) Formation of mesoporous structure: 1) Adding a template: dissolving hexadecyltrimethylammonium bromide or polyethylene oxide as a template in a mixed solution of deionized water and ethanol, adding Fe3O4 particles coated with SiO2, and dispersing by ultrasonication; 2) Formation of mesoporous shell: under stirring conditions, tetraethoxysilane is added dropwise and the reaction is continued by stirring; 3) Cleaning and drying: Collect the samples by magnetic separation and wash them with ethanol and deionized water in sequence; (3) Removal of template: 1) Place the sample in a ceramic crucible and program the temperature; 2) maintaining a constant temperature for calcination to remove hexadecyltrimethylammonium bromide or polyethylene oxide; Step 5: Prepare magnetizable grouting liquid: Fe3O4@SiO2 mesoporous microspheres, cement, water and anti-dispersant are added into the mixing tank of the vehicle-mounted mixing and pouring machine at a mass ratio of 100:400:100:2 for preparation. The preparation process is as follows: (1) First add cement, then add Fe3O4@SiO2 mesoporous microspheres, and mix the two evenly; (2) Add water and stir evenly; (3) Add anti-dispersant and stir evenly; Step 6: Grouting: When the porous asphalt mixture is confirmed to be cooled, the cement-based magnetizable grouting liquid is poured through the vehicle-mounted mixing and pouring machine; Step 7: Scraping: After pouring, when there are no more bubbles coming out of the pores of the asphalt mixture, scraping should be carried out. The scraping must be done before the mortar surface is crusted. Use a rubber scraper to scrape off the excess mortar on the surface to expose the aggregate of the asphalt mixture. In addition, the scraping must be done in the same direction to avoid scratches. At this point, the construction is completed.

Citation Information

Patent Citations

  • Graphene oxide-ferroferric oxide magnetic liquid-cement based composite material and preparation method thereof

    CN108314380A

  • Quick-hardening rustless cement based grouting material

    CN108623264A

  • Semi-flexible pavement material and construction method

    CN110818358A

  • Pouring type flexible pavement and preparation method thereof

    CN113816653A

  • Pouring type self-bright asphalt pavement upper surface layer as well as preparation process and application thereof

    CN113897835A

Cited By

  • Basalt rib and steel fiber reinforced road cover plate and preparation method thereof

    CN120247503A

  • Emulsified asphalt type asphalt grouting material modified by rare earth tailings and application of emulsified asphalt type asphalt grouting material

    CN121136468A

  • Rare earth tailings modified emulsified asphalt asphalt grouting material and application thereof

    CN121136468B

  • Steel bridge deck pavement method based on magnetic force effect

    CN121496837A

  • Steel bridge deck pavement method based on magnetic force effect

    CN121496837B